La tutoría y la orientación universitaria en la nueva coyuntura de la enseñanza superior : el programa "Velero" - Pedro R. Álvarez Pérez (Universidad de La Rioja, 2013)
This article approach tutoring at the University level in the context of the rapid changes that are undergoing European Universities as a result of the Bolonia Agreements. In these troubled waters, it seems that one of the main trends points to the relevance attached to students learning processes and the correponding tutorial role of University teachers. To facilitate the enacting of that role we have designed the VELERO program, in order to support and foster the processes of adaptation and professional, academic and personal development of first year university students.